Implementasi Theory of Planned Behavior terhadap Pemasaran Usaha Kecil Menengah melalui E-Commerce - Darsono, Junianto Tjahjo; Susana, Erni; Prihantono, Eko Yuni (Jurnal Manajemen dan Kewirausahaan, 2020)
Theory of Planned Behavior (TPB) has supported relationships for predicting many different people's behaviors. TPB shows that the proximal determinant of will behavior is one's intention to engage in that behavior. Attitudes and subjective norms are suggested to exert its effects of behavior through intention. The TPB model is also developed and was further refined based on the results of the model trials conducted using data collected in Malang. The purpose of this study is to analyze the influence of attitudes, subjective norms, and behavioral control on intentions and the translation process will then occur in the behavior of SMEs in marketing through e-commerce. The population in this study is the SMEs in Malang. The sampling technique is simple random sampling. Data analysis techniques use Structural Equation Modeling (SEM) analysis. The results of this study indicate: 1) attitudes, subjective norms, and behavioral control affect the intention, and 2) the intention variable mediates the effect of attitudes, subjective norms, and behavioral control on the behavior of SMEs in marketing through e-commerce by SMEs in Malang.https://doi.org/10.26905/jmdk.v8i2.5098Â